Enhancing Preschool English Literacy through Mobile 3D Pyramid Holograms: The PyraRead Study - Mohd Barkhaya, Nurul Maziah (International Journal of Interactive Mobile Technologies (iJIM), 2026)
The literacy issue in preschool language learning has been highlighted worldwide, particularly due to the lack of visualization experiences using three-dimensional (3D) tools. Holograms, as part of current technological trends in education, have emerged as a promising solution. A type of reflective hologram known as the three-dimensional pyramid hologram (3DPH) has the potential to visualize content in a life-like manner, thereby enhancing children’s interactions and understanding through meaningful visual experiences. This study aims to examine the effects of a mobile-based 3DPH application called PyraRead (Pyramid for Reading) in enhancing preschool children’s English literacy. By delivering interactive 3D holographic content via mobile devices, PyraRead enables flexible and engaging learning experiences beyond traditional classroom tools. This study investigates both children’s achievement and their interactions, including their engagement with the mobile PyraRead and with peers. A quasiexperimental design was employed. The results showed that children who used the mobile PyraRead demonstrated improved English literacy, and 12 out of the 15 observed interaction behaviors were positively associated with their learning outcomes. These findings suggest that learning through the mobile PyraRead effectively promotes children’s interactions and engagement, ultimately contributing to improvements in their English literacy skills. Although based on a modest sample, the study provides early evidence of the potential of mobile 3DPH tools to enrich preschool literacy learning through immersive and interactive experiences.